Agents of Things (AoT): An intelligent operational concept of the Internet of Things (IoT) - Mzahm A.M.; Ahmad M.S.; Tang A.Y.C. (IEEE Computer Society, 2023)
In this conceptual paper, we review the definitions, characteristics, and architecture of the Internet of Things (IoT) concept. We then identify the deficiencies of the IoT concept, analyze them, and discover the issue of lack of reasoning and intelligence in the IoT concept. We propose a solution to augment the IoT with intelligent software agents resulting in a new concept called the Agents of Things (AoT). The paper presents the AoT architecture and a scenario for one application of the proposed concept. Finally, it discusses the benefits of implementing AoT concept to solve real world issues and the future work. © 2013 IEEE.